2022
DOI: 10.3390/su14042334
|View full text |Cite
|
Sign up to set email alerts
|

The One Thing You Need to Change Is Emotions: The Effect of Multi-Sensory Marketing on Consumer Behavior

Abstract: Retailers are increasingly aware of the importance of store atmosphere on consumers’ emotions. The results of four experimental studies demonstrate that the sensory cues by which customers sense products and the amount of (in)congruency among the sensory stimuli of the products affect consumers’ emotions, willingness to purchase, and experience. In the presence of moderators such as colors, jingles, prices, and scent imagery, when facing sensory-rich experiential products (e.g., juice, coffee, hamburger, soda)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
0
18
0
2
Order By: Relevance
“…Advertisements and marketing campaigns frequently portray energy drinks as fashionable, pleasurable, or necessary for optimal performance, affecting consumer behaviors and attitudes ( 23 , 54 ). A study in Canada indicated a considerable number of energy drink postings on social media in 2020–2021, with several posts have using marketing strategies on Twitter, Facebook and Instagram, that may be appealing to adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advertisements and marketing campaigns frequently portray energy drinks as fashionable, pleasurable, or necessary for optimal performance, affecting consumer behaviors and attitudes ( 23 , 54 ). A study in Canada indicated a considerable number of energy drink postings on social media in 2020–2021, with several posts have using marketing strategies on Twitter, Facebook and Instagram, that may be appealing to adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Advertisements and marketing campaigns often depict these beverages as stylish, enjoyable, or vital for peak performance, thereby influencing consumer attitudes and actions. Moreover, the ubiquitous presence and societal acceptance of these drinks in different contexts (like social gatherings, workplaces, and vending machines) can encourage regular consumption ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multisensorisches Marketing schafft eine umfassende Markenerfahrung durch gezielte Ansprache mehrerer Sinne [3]. Die Komponenten umfassen: ▪ Visuelle Reize: Gestaltung von Elementen wie Verpackung, Werbung und Ladenlayout, wobei Farben, Formen und Bilder eine entscheidende Rolle spielen [4].…”
Section: Multisensorisches Marketing Im Dienst Gesunder Ernährungunclassified
“…Multisensorisches Marketing zielt darauf ab, alle Sinne des Kunden anzusprechen, indem es visuelle, auditive, gustatorische, olfaktorische und haptische Elemente in die Markenkommunikation integriert [3]. Diese strategische Ausrichtung intensiviert nicht nur die Wahrnehmung von Marken, sondern fördert auch eine tiefere emotionale Bindung zwischen Konsumenten und Produkten.…”
Section: Potenzialunclassified
“…Furthermore, it is advised that future studies should employ a mixedmethod data collection technique as it provides a better understanding of the phenomenon. Finally, as this study examined Saudi tourists who were willing to visit the UK, it is advised that future research investigate the phenomenon between different countries [75][76][77][78][79].…”
Section: Implications and Future Researchmentioning
confidence: 99%